Oil spill detection and monitoring in the Cyprus region - Melillos, George; Kalogirou, Eleftheria; Makri, Despina; Hadjimitsis, Diofantos G. (My University, 2023)
Cyprus can be found in a critical location, a geostrategic location among Asia, North Africa, and Europe. This is particularly important, thus, can affect the marine environment with the vessels that pass through the sea. A severe form of pollution can be an oil spill. An oil spill is a liquid, usually petroleum hydrocarbon, released to the sea and can affect the marine ecosystem and humans. Oil spills can be recorded as marine incidents or accidents. In August 2021, one of the essential accidental oil spills came from the northeast coast of Syria. In the present study, we will try to implement a spatial analysis of oil spill detection by combing remote sensing techniques and monitoring, using the Sentinel Application Platform (SNAP) and the consequences that follow this procedure. The implementation was made using two different polarization; vertical polarization (VV) and horizontal comparison (VH). The preliminary results show that the Sentinel-1 SAR data would give effective results and spatial information on oil spill detection to decision-makers.
Keywords: Oil spill; SAR; Sentinel-1; Cyprus; Marine; Security